2014
DOI: 10.1039/c4pp00085d
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and calorimetric investigation on the structural reorganization of poly(A) by phenothiazinium dyes azure A and azure B

Abstract: Poly(A) has significant relevance to mRNA stability, protein synthesis and cancer biology. The ability of two phenothiazinium dyes azure A (AA) and azure B (AB) to bind single-stranded poly(A) was studied by spectroscopic and calorimetric techniques. Strong binding of the dyes and the higher affinity of AA over AB were ascertained from absorbance and fluorescence experiments. Significant perturbation of the circular dichroism spectrum of poly(A) in the presence of these molecules with formation of induced CD b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…In the present case, the TD bind S o value is positive and the binding was favored by both enthalpy and entropy changes. Similar results were reported in some cases where small molecules induced self-assembled structure in poly(A) [8,9,11]. The origin of the strong positive entropy change may also be due to cation release and change in water structure as postulated in many previous small molecule-nucleic acid interactions [39][40][41].…”
Section: Isothermal Titration Calorimetrysupporting
confidence: 82%
See 1 more Smart Citation
“…In the present case, the TD bind S o value is positive and the binding was favored by both enthalpy and entropy changes. Similar results were reported in some cases where small molecules induced self-assembled structure in poly(A) [8,9,11]. The origin of the strong positive entropy change may also be due to cation release and change in water structure as postulated in many previous small molecule-nucleic acid interactions [39][40][41].…”
Section: Isothermal Titration Calorimetrysupporting
confidence: 82%
“…Binding of small molecules to poly(A) tail of mRNA could alter its conformation, prevent elongation or create alternate conformations, leading to switching off of protein synthesis. A number of alkaloids and other small molecules have recently been found to induce a unique self-assembled structure in poly(A) in vitro [4][5][6][7][8][9][10][11][12]. The effects of such transformations if mimicked in vivo may be very interesting for arresting cell division.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pH of the buffer solution remained more or less unchanged in this temperature range as measured, the reactants and products contain groups that can ionize and some variation Enthalpy-entropy compensation is a significant phenomenon that is associated with solvent reorganization accompanying drug-nucleic acid interactions [30,[34][35][36][37][38][39].…”
Section: Temperature Dependent Isothermal Titration Calorimetry Of Dymentioning
confidence: 83%
“…The K value decreased on increasing the [K + ] from 50 to 130 mM. Earlier studies on the induction of self-structure by small molecules like methylene blue, chelerythrine, proflavine, azure A and azure B have shown that the K value increases with increase in salt concentration [30,32,34,35]. However, in the case of coralyne here the K values decreased from {(3.12 ± 0.12)Á10 6 to (2.46 ± 0.11)Á10 6 to (1.91 ± 0.09)}Á10 6 M À1 on increasing the [K + ] from {(50 ± 0.01) to (75 ± 0.01) to (100 ± 0.01)} mM.…”
Section: Temperature Dependent Calorimetric Studiesmentioning
confidence: 92%
“…Poly(A) has single stranded helical structure at neutral pH but some small molecules and alkaloids can induce unique self-structure (double stranded) in poly(A) at neutral pH where otherwise only single stranded structure can exist [13,15,[26][27][28][29][30][31][32][33][34][35]. Such self-structure induction can influence mRNA degradation and stop protein production in the cell.…”
Section: Introductionmentioning
confidence: 99%